ANALYSIS OF DESTINATION ATTRIBUTE AND QUALITY PERCEPTION OF ACEH HALAL TOURISM INTENTION: THE MEDIASION ROLE OF VISITOR SATISFACTION - Fuadi Fuadi; Reza Juanda; Munardi Munardi; Falahuddin F (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
The COVID-19 pandemic is considered different from previous pandemics because of the extent and number of people infected. The impact of the COVID-19 pandemic has made almost all joints of the world economy sluggish, as a result it is estimated that the world economy will be in a recession. This also applies in Indonesia, where economic growth is not as expected. One of the sectors most impacted by this virus is the tourism industry and its derivatives, so it is very important to know and determine the right strategy in managing and seeing tourism opportunities in the midst of the pandemic and the aftermath as an effort to develop the world of sustainable tourism. The purpose of this study was to determine the impact of tourist satisfaction and perceived quality on the intention of halal tourism in the midst of a pandemic and in the future. Research on travel intentions in the midst of a pandemic, especially during the COVID-19 period, is still very limited, so that it will have an impact in the future, so further research needs to be carried out in a different context from the limitations of previous research. The research stages include; data observation, determining the main problem, the purpose of the activity, literature study, data collection, data processing, analysis of results, and evaluation of research results. This research is based on the theoretical framework of Destination Attributes and Perceived Quality. This study seeks to analyze the intentions of tourists traveling in the midst of the COVID-19 pandemic among the people of Aceh, Indonesia, and world tourists who travel to Banda Aceh City, Aceh Province. The data analysis method used a partial least squares (PLS) statistical approach with the structural equational model (SEM) method to see the direct and indirect effects (mediation). The findings of this study are expected to contribute to more effective planning for restoring the tourism business, specifically halal tourism and for the development of measures for destination attributes and visitor satisfaction and security in tourism services, now and in the future. The outputs in this study consist of research reports, articles in accredited national journals and produce HKI (copyright). The resulting TKT level of research is TKT 3.